(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Magnetic resonance cholangiopancreatography (MRCP) is a valuable method for the evaluation of Biliary Ducts obstruction and a valuable alternative to endoscopic retrograde cholangiopancreatography (ERCP). It is noninvasive and does not require the use of contrast material or ionizing. To evaluate the accuracy of magnetic resonance (MR) cholangiopancreatography in the diagnosis of Biliary Ducts Obstruction